Case study on challenges in research with public partners: A personal data incident during recruitment for a survey study on ageing and housing - Magnus Zingmark; Susanne Iwarsson (BMC Research Notes)
Abstract Objective To highlight experiences from a personal data incident, which occurred during recruitment for a project focused on how housing choices and relocation are related to active and healthy ageing. Results Based on established collaboration, the researchers and representatives of housing companies planned for recruitment. Invitations to participate was distributed to persons registered with an interest in relocation. The invitation letter included information according to ethical requirements and a link to an online survey. Within a few days, the housing company was contacted by a person who had received the invitation stating that the company had not secured individual consent to the disclosure of personal data to the researchers. The company and the researchers initiated a range of immediate actions to manage the situation, including a plan for how to respond to persons who wanted their person data to be deleted, how to handle already collected data, and for the continued implementation of the recruitment process. We acknowledge that despite established collaboration based on long term commitment from all parties involved, ethical issues require constant attention. Whereas our case represents a hard-learned lesson on a sensitive ethical issue, the well-established collaboration was of paramount importance for how the situation was handled.